Comparison of maternal outcomes in caring by Doula, trained lay companion and routine midwifery care - Shirin Shahbazi Sighaldeh; Afsaneh Azadpour; Katayoun Vakilian; Abbas Rahimi Foroushani; Seyedeh Fatemeh Vasegh Rahimparvar; Sedigheh Hantoushzadeh (BMC, 2023)
Abstract Introduction The aim of this study was to compare maternal and neonatal outcomes in the care provided by Doula, trained lay companion, and routine midwifery care in the labor and obstetric units. In this study, only results related to maternal outcomes were presented. Method This is a quasi-experimental study, which was conducted on 150 women with low-risk pregnancies who had been selected for vaginal birth at private clinics and public hospitals of Arak, Iran. Participants were divided into three groups, two intervention groups, doula and trained lay companion, and one control group, midwife's routine care. The intervention groups, in addition to receiving routine care from the labor and maternity units, also received support and training by doula or a trained lay companion, but 50 the control group received only routine midwifery care. In the control group and the trained companion, the samples were taken from 10 clinics of different parts of the city by random sampling method using the SIB center system. Then, among selected numbers, we randomly selected samples for each group. But in Doula group, because of limited number of samples, convenience sampling was used and all women enrolled in doula care were included in the study until the number reached 50. In each group, outcomes such as the duration of active phase and second stage of labor, as well as the severity of pain, anxiety and maternal satisfaction with birth were measured and compared with other groups. Data were collected by a researcher-made checklist, the Spielberger's State-Trait Anxiety Inventory (STAI), the Pain Visual Assessment Scale (VAS), and the Hollins Martin's Birth Satisfaction Scale-Revised (BSS-R). Data were analyzed by SPSS-22 statistical software using Kruskal Wallis, Chi-Square, ANOVA and Fisher's exact tests. Findings Based on the results, the mean duration of active phase between three groups was 234.68 ± 118.74, 256.66 ± 108.75 and 279 ± 94.37 min, respectively (p = 0.022). Also, the mean duration of second stage in three groups was 10 ± 5.61, 10.35 ± 5.1 and 22.30 ± 75.57 min, respectively (p < 0.001). The difference between mean pain scores in the first, second, third, fourth and fifth hours was not statistically significant. The average difference in anxiety score in the two stages of labor was higher in the lay companion group, and this difference was statistically significant (p < 0.001); however, the level of satisfaction in doula group was higher compared to the lay companion and control groups (p < 0.00 1). Conclusion According to present study, doula care has a greater effect on reducing the duration of labor than other care models. Based on the study, there was no statistically significant difference between the three groups in terms of variables such as the severity of labor pain. However, the level of anxiety of pregnant mothers in the group supported by lay companion was lower than the other two groups, which indicates the positive effect of mothers' training on increasing maternal comfort and satisfaction. It is suggested that further research investigate the severity of labor pain in groups supported by different care models and also we recommend the use of lay companion' support during childbearing of mothers who could not afford doula. Trail registration This article has been registered in Iran's Clinical Trial Center with the code: IRCT20230620058548N1. 2023/08/29.